2015
DOI: 10.1590/1678-775720140339
|View full text |Cite
|
Sign up to set email alerts
|

The effects of frenotomy on breastfeeding

Abstract: Although the interference of tongue-tie with breastfeeding is a controversial subject, The use of lingual frenotomy has been widely indicated by health professionals. Objective: To observe changes in breastfeeding patterns after lingual frenotomy concerning the number of sucks, pause length between groups of sucking and mother's complaints.Material and Methods : Oral yes/no questions about breastfeeding symptoms and sucking/swallowing/breathing coordination were answered by the mothers of 109, 30 day old infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 14 publications
5
55
3
15
Order By: Relevance
“…Martinelli et al in 2015 demonstrated that, after a lingual frenotomy, babies with a short lingual frenulum show changes that favour the appropriate standards of breastfeeding and all the symptoms reported by the mothers improved [2]. Furthermore, Power and Murphy in 2015 conclude that 50% of the breastfed babies with ankyloglossia will not encounter any problems [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinelli et al in 2015 demonstrated that, after a lingual frenotomy, babies with a short lingual frenulum show changes that favour the appropriate standards of breastfeeding and all the symptoms reported by the mothers improved [2]. Furthermore, Power and Murphy in 2015 conclude that 50% of the breastfed babies with ankyloglossia will not encounter any problems [5].…”
Section: Discussionmentioning
confidence: 99%
“…The limitation in lingual mobility in newborns is another one of the reasons that can compromise sucking and latching on to the breast during the breastfeed [2, 47]. …”
Section: Introductionmentioning
confidence: 99%
“…The nipple is compressed from the tip to the base when the tongue is high, and, when it lowers, the nipple expands by approaching the hard palate with the soft palate and increases in diameter, causing a vacuum and allowing the milk to flow into the intraoral space [8][9][10][11]. Alterations of the lingual frenulum may limit its mobility [8,[12][13][14][15]33,34], resulting in inadequate catching and potentially leading to changes in sucking function, especially in the dynamic of sucking/removal of milk. The main problems identified in cases of an altered lingual frenulum in relation to breastfeeding in the mother's womb are difficulties in catching, nipple pain and cracking, prolonged feeding times, reduced milk intake by the infant, the loss of weight [12,14,[34][35][36][37], dehydration, and growth deficiency [9,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…After apoptosis, the remaining residual embryonic tissue (lingual frenulum) may limit tongue movements to varying degrees. This congenital oral anomaly is referred to as ankyloglossia [9] and may cause reduced mouth opening, imprecision, and restriction of isolated tongue movements, a heart-shaped tip, downward protrusion [13], the tongue to rest on the floor of the mouth, and difficulties in sucking, chewing, swallowing, and speech functions, among others [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The conceptualization stage included the following definitions: the target audience, the aim, the analysis and the definition of the content based on a literature review on tongue-tie, infants' lingual frenulum assessment, and frenotomy 2,3; [13][14][15][16][17][18][19] . Subsequently, the website content was defined and organized.…”
Section: Methodsmentioning
confidence: 99%